2022
DOI: 10.1038/s41419-022-04747-3
|View full text |Cite
|
Sign up to set email alerts
|

RBMS1 promotes gastric cancer metastasis through autocrine IL-6/JAK2/STAT3 signaling

Abstract: Metastasis is the most important reason for the poor prognosis of gastric cancer (GC) patients, and the mechanism urgently needs to be clarified. Here, we explored a prognostic model for the estimation of tumor-associated mortality in GC patients and revealed the RNA-binding protein RBMS1 as a candidate promoter gene for GC metastasis by analyzing GOBO and Oncomine high-throughput sequencing datasets for 408 GC patients. Additionally, RBMS1 was observed with overexpression in 85 GC patient clinical specimens b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 26 publications
3
23
0
Order By: Relevance
“…Immunohistochemical analysis of the HPA database indicated that the protein products of risk-associated genes were expressed at higher levels in GC samples than in normal samples ( Figure 5I ). Immunohistochemical images of RBMS1 were obtained from a recent study ( Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical analysis of the HPA database indicated that the protein products of risk-associated genes were expressed at higher levels in GC samples than in normal samples ( Figure 5I ). Immunohistochemical images of RBMS1 were obtained from a recent study ( Liu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“… Liu et al (2022) found that ACTA2-AS1 (lncRNA) suppressed the malignant phenotype of GC cells by targeting the miR-378a-3p/PLCXD2 axis as ceRNA. Liu et al (2022) revealed the potential molecular mechanism of RBMS1 to promote GC metastasis, suggesting that RBMS1 may be a potential therapeutic target. In addition, Durr et al (2022) suggested that KCNQ1OT1 and miR-378a may regulate mt-ATP6 content through the ceRNA axis, which may provide a pathway for the treatment of type 2 diabetic heart.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal S100A4 stimulates STAT3 signaling to mediate resistance of lung tumor cells to the immune system [ 49 , 50 ]. Moreover, high expression of STAT3 mediated by IL-6 can promote invasion and metastasis of gastric cancer cells [ 51 ]. The presence of a high-fat diet due to cyclophilin B is significant in inducing STAT3 signaling to increase PVT1 expression.…”
Section: Stat3 Signaling: An Overviewmentioning
confidence: 99%
“…Zhang et al (138) also found that activated STAT3 was positive in early GC, poorly differentiated adenocarcinoma and metastatic lymph node tissue. Liu et al (7) elucidated the potential molecular mechanism of RBMS1 promoting GC metastasis: RBMS1transactivates IL-6 and stimulates JAK2/STAT3 pathway based on in vitro and in vivo experiments.…”
Section: Gastric Cancermentioning
confidence: 99%
“…A large number of studies have shown that IL-6/JAK2/ STAT3 signaling pathway is abnormally highly activated in a variety of cancers, such as gastric cancer (GC) (6,7), breast cancer (BC) (8)(9)(10), liver cancer (11-13), colorectal cancer (CRC) (14,15), colon cancer (16, 17), ovarian cancer (OC) (18,19), lung cancer (20-22), pancreatic cancer (PC) (4,5). It strongly inhibits anti-tumor immune response (23).…”
Section: Introductionmentioning
confidence: 99%